Polymer composite, method for use thereof, low dielectric resin composition, prepreg, and metal foil laminate
By using a polymer composite material containing two styrene-based copolymers, a low dielectric resin composition was prepared, which solved the problem of high dielectric loss in high-frequency 5G communication, and improved signal quality and material processability were achieved.
Patent Information
- Application Number
- CN202411415144.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-12
- Filing Date
- 2024-10-11
- Publication Date
- 2025-04-15
AI Technical Summary
It is difficult to develop copper clad foil laminate materials with low dielectric loss, especially in high-frequency 5G communications, where dielectric loss affects signal quality.
Using a polymer composite material containing two styrene-based copolymers, a low dielectric resin composition with a low dielectric loss tangent was prepared by adjusting the weight ratio and molecular weight of the first styrene-based copolymer and the second styrene-based copolymer.
It realizes reducing dielectric loss in high-frequency 5G communication, improving signal transmission and reception quality, and improving material processability and fluidity.
Smart Images

Figure CN119823516A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a polymer composite material, its use, a low dielectric resin composition, a prepreg, and a metal foil laminate. In particular, the present invention relates to a polymer composite material comprising two styrene copolymers, its use, a low dielectric resin composition, a prepreg, and a metal foil laminate. Background Art
[0002] The fifth generation mobile network technology (5G mobile network technology for short) is the latest generation of mobile communication technology. 5G mobile communication technology has the characteristics of high-speed transmission, wide connection, and low latency. At present, 5G mobile communication technology can be divided into three types according to the frequency band used: high-frequency 5G, medium-frequency 5G, and low-frequency 5G. High-frequency 5G can provide ultra-high connection speed.
[0003] However, the quality of signal reception and transmission will be affected by high-frequency path loss, conductor loss, and dielectric loss during the high-frequency 5G transmission and reception process. Therefore, it is necessary to develop copper clad laminate (CCL) materials with low dielectric loss to reduce the dielectric loss of high-frequency 5G during the transmission and reception process, thereby improving the quality of signal reception and transmission.
[0004] The goal of reducing dielectric loss can be achieved by reducing the dielectric properties (dielectric constant (Dk) and / or dielectric loss tangent (Df)) of the metal foil substrate. In addition to the requirements for dielectric properties, typical compositions also encounter difficulties in processability and fluidity. This poor fluidity leads to insufficient filling performance, which makes the product unusable. Therefore, people are still seeking a material and resin composition with lower dielectric loss and better processability. Summary of the invention
[0005] In view of the above problems, the present invention provides a polymer composite material for preparing a low dielectric resin composition with low dielectric loss tangent (Df), a low dielectric resin composition containing the same, a prepreg made from the low dielectric resin composition, and a metal foil laminate containing the prepreg.
[0006] In one embodiment of the present invention, a polymer composite material for preparing a low dielectric resin composition is provided, wherein the low dielectric resin composition has a dielectric loss tangent (Df) less than or equal to 0.00200. The polymer composite material comprises a first styrene copolymer having a weight average molecular weight lower than 20,000 g / mol, and a second styrene copolymer having a weight average molecular weight higher than 20,000 g / mol, wherein the weight ratio of the first styrene copolymer to the second styrene copolymer is 5 / 95 to 95 / 5.
[0007] In one embodiment of the present invention, a polymer composite material for preparing a low dielectric resin composition is provided, wherein the low dielectric resin composition has a dielectric loss tangent (Df) less than or equal to 0.00200. The polymer composite material comprises a first styrene copolymer that is liquid at 25°C, and a second styrene copolymer that is solid at 25°C, wherein the weight ratio of the first styrene copolymer to the second styrene copolymer is 5 / 95 to 95 / 5.
[0008] In one embodiment of the present invention, a method for using a polymer composite material is provided, the method comprising: using the polymer composite material to form a mixture containing a hydrocarbon resin to manufacture a metal foil laminate having a dielectric loss tangent (Df) less than or equal to 0.00200. The polymer composite material comprises a first styrene copolymer having a weight average molecular weight less than 20,000 g / mol, and a second styrene copolymer having a weight average molecular weight greater than 20,000 g / mol, wherein the weight ratio of the first styrene copolymer to the second styrene copolymer is 5 / 95 to 95 / 5.
[0009] In one embodiment of the present invention, a low dielectric resin composition is provided, wherein the low dielectric resin composition comprises a first styrene copolymer having a weight average molecular weight lower than 20,000 g / mol, and a second styrene copolymer having a weight average molecular weight higher than 20,000 g / mol, wherein the weight ratio of the first styrene copolymer to the second styrene copolymer is 5 / 95 to 95 / 5, and the low dielectric resin composition has a dielectric loss tangent (Df) less than or equal to 0.00200.
[0010] In one embodiment of the present invention, a low dielectric resin composition is provided, wherein the low dielectric resin composition comprises a first styrene copolymer that is liquid at 25° C. and a second styrene copolymer that is solid at 25° C., wherein the weight ratio of the first styrene copolymer to the second styrene copolymer is 5 / 95 to 95 / 5, and the low dielectric resin composition has a dielectric loss tangent (Df) less than or equal to 0.00200.
[0011] In one embodiment of the present invention, a low dielectric resin composition is provided, which comprises a hydrocarbon resin, a first styrene copolymer having a weight average molecular weight lower than 20,000 g / mol, and a second styrene copolymer having a weight average molecular weight higher than 20,000 g / mol.
[0012] In one embodiment of the present invention, a low dielectric resin composition is provided, wherein the low dielectric resin composition comprises a hydrocarbon resin, a first styrene copolymer that is liquid at 25° C., and a second styrene copolymer that is solid at 25° C.
[0013] In one embodiment of the present invention, a prepreg is provided, which is made of a low dielectric resin composition comprising a polymer composite material, wherein the polymer composite material comprises a first styrene copolymer having a weight average molecular weight lower than 20,000 g / mol, and a second styrene copolymer having a weight average molecular weight higher than 20,000 g / mol, wherein the weight ratio of the first styrene copolymer to the second styrene copolymer is 5 / 95 to 95 / 5.
[0014] In one embodiment of the present invention, a prepreg is provided, which is made of a low dielectric resin composition comprising a polymer composite material, wherein the polymer composite material comprises a first styrene copolymer which is liquid at 25°C, and a second styrene copolymer which is solid at 25°C, wherein the weight ratio of the first styrene copolymer to the second styrene copolymer is 5 / 95 to 95 / 5.
[0015] In one embodiment of the present invention, a prepreg made of a low dielectric resin composition is provided, wherein the low dielectric resin composition comprises a hydrocarbon resin, a first styrene copolymer having a weight average molecular weight lower than 20,000 g / mol, and a second styrene copolymer having a weight average molecular weight higher than 20,000 g / mol.
[0016] In one embodiment of the present invention, a prepreg made of a low dielectric resin composition is provided. The low dielectric resin composition comprises a hydrocarbon resin, a first styrene copolymer that is liquid at 25°C, and a second styrene copolymer that is solid at 25°C.
[0017] In one embodiment of the present invention, a metal foil laminate is provided. The metal foil laminate comprises a prepreg made of a low dielectric resin composition containing a polymer composite material. The polymer composite material comprises a first styrene copolymer having a weight average molecular weight lower than 20,000 g / mol, and a second styrene copolymer having a weight average molecular weight higher than 20,000 g / mol, wherein the weight ratio of the first styrene copolymer to the second styrene copolymer is 5 / 95 to 95 / 5.
[0018] In one embodiment of the present invention, a metal foil laminate is provided. The metal foil laminate comprises a prepreg made of a low dielectric resin composition containing a polymer composite material. The polymer composite material comprises a first styrene copolymer that is liquid at 25° C. and a second styrene copolymer that is solid at 25° C., wherein the weight ratio of the first styrene copolymer to the second styrene copolymer is 5 / 95 to 95 / 5.
[0019] In one embodiment of the present invention, a metal foil laminate is provided. The metal foil laminate comprises a prepreg made of a low dielectric resin composition. The low dielectric resin composition comprises a hydrocarbon resin, a first styrene copolymer having a weight average molecular weight lower than 20,000 g / mol, and a second styrene copolymer having a weight average molecular weight higher than 20,000 g / mol.
[0020] In one embodiment of the present invention, a metal foil laminate is provided. The metal foil laminate comprises a prepreg made of a low dielectric resin composition. The low dielectric resin composition comprises a hydrocarbon resin, a first styrene copolymer that is liquid at 25°C, and a second styrene copolymer that is solid at 25°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to make the purpose, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below with reference to the accompanying drawings, wherein:
[0022] Figure 1 is a schematic diagram of a metal foil laminate according to an embodiment of the present invention.
[0023]
Explanation of symbols
[0024] 10: Metal foil laminate
[0025] 101: Base
[0026] 103: polymer layer
[0027] 105: Adhesion layer DETAILED DESCRIPTION
[0028] It will be further understood that when "include" and / or "comprising" are used in this specification, they specifically refer to the presence of the characteristic components, integers, steps, operations, components, ingredients, and / or groups thereof, but do not exclude the presence or addition of one or more other characteristic components, integers, steps, operations, components, ingredients, and / or groups thereof. When the singular form "a" or "an" is used in this specification, it is intended to include the plural form unless the context clearly indicates otherwise.
[0029] It will be understood that although the terms "first", "second", etc. may be used herein to describe various components, elements, regions, layers and / or parts, these components, elements, regions, layers and / or parts should not be limited by these terms. These terms are only used to distinguish one component, element, region, layer or part from another component, element, region, layer or part, and do not imply any particular order therebetween.
[0030] It will be understood that the terms "about", "approximately", and "roughly" herein are generally meant to be within 20% of a given value or range, preferably within 10%, and more preferably within 5%, or within 3%, or within 2%, or within 1%, or within 0.5%. The quantity given here is an approximate quantity, that is, in the absence of a specific description of "about", "approximately", "roughly", the meaning of "about", "approximately", and "roughly" may still be implied. Further, the numerical values represented in the present invention may include the numerical values and deviation values within the deviation range acceptable to those with ordinary knowledge in the art. It will be understood that the expressions "a to b" or "a to b" used herein to represent a specific numerical range are defined as "≧a and ≦b".
[0031] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meanings as those commonly understood by those skilled in the art. It is understood that these terms, such as those defined in commonly used dictionaries, should be interpreted as having a meaning consistent with the background or context of the relevant technology and the present application, and should not be interpreted in an idealized or overly formal manner unless specifically defined in the present invention. The following will omit descriptions that may unnecessarily confuse the known functions and structures of the present invention.
[0032] In the present invention, "C 1-20 "Alkyl" refers to a straight chain, branched chain or cyclic aliphatic hydrocarbon monovalent group having 1 to 20 carbon atoms in the main carbon chain.1-4 "Alkyl" refers to a straight chain, branched chain or cyclic aliphatic hydrocarbon monovalent group having 1 to 4 carbon atoms in the main carbon chain. 1-20 Non-limiting examples of alkyl groups include, but are not limited to, methyl, ethyl, propyl, isobutyl, sec-butyl, tert-butyl, pentyl, isopentyl, hexyl, dodecyl, dodecyl, cyclohexyl, cyclooctyl, and cyclododecyl. 1-4 Non-limiting examples of alkyl groups include, but are not limited to, methyl, ethyl, and propyl.
[0033] In the present invention, "C 2-20 "Alkenyl" refers to a linear, branched or cyclic aliphatic hydrocarbon monovalent group having 2 to 20 carbon atoms and at least one carbon-carbon double bond in the main carbon chain. 2-20 Non-limiting examples of alkenyl groups include, but are not limited to, ethenyl, propenyl, isobutenyl, sec-butenyl, tert-butenyl, pentenyl, isopentenyl, hexenyl, decenyl, dodecenyl, pentadecenyl, cyclohexenyl, cyclooctenyl, cyclopentenyl, cyclopentadienyl, and cyclopentadecenyl.
[0034] In the present invention, "having C 1-20 The term "alkane-chain carboxylate group" refers to a group having the structure A group, wherein "*" indicates a connection site to other groups, wherein R 1 C 1-20 Alkyl, R 2 is a single bond or C 1-20 Alkyl, and R 1 and R 2 The sum of the carbon numbers of the alkyl groups on the main carbon chain is 1 to 20.
[0035] In one embodiment of the present invention, a polymer composite material for preparing a low dielectric resin composition is provided, wherein the low dielectric resin composition has a dielectric loss tangent (Df) less than or equal to 0.00200. The polymer composite material comprises a first styrene copolymer and a second styrene copolymer different from the first styrene copolymer, wherein the weight ratio of the first styrene copolymer to the second styrene copolymer is 5 / 95 to 95 / 5. In some embodiments, the weight ratio of the first styrene copolymer to the second styrene copolymer can be in the range of 10 / 90 to 90 / 10, 20 / 80 to 80 / 20, or 25 / 75 to 80 / 20. In some embodiments, the weight ratio of the first styrene copolymer to the second styrene copolymer can be 5 / 95, 10 / 90, 15 / 85, 20 / 80, 25 / 75, 30 / 70, 35 / 65, 40 / 60, 45 / 55, 50 / 50, 55 / 45, 60 / 40, 65 / 35, 70 / 30, 75 / 25, 80 / 20, 85 / 15, 90 / 10, or 95 / 5, but the present invention is not limited thereto.
[0036] In some embodiments, the first styrenic copolymer has a weight average molecular weight of less than 20,000 g / mol, and the second styrenic copolymer has a weight average molecular weight of greater than 20,000 g / mol, but the invention is not limited thereto. In some embodiments, the first styrenic copolymer is liquid at 25°C, and the second styrenic copolymer is solid at 25°C.
[0037] In the embodiment where the first styrene copolymer has a weight average molecular weight lower than 20,000 g / mol and the second styrene copolymer has a weight average molecular weight higher than 20,000 g / mol, the molecular weight of the first styrene copolymer is determined by gel permeation chromatography (GPC). In some embodiments, the first styrene copolymer may have a weight average molecular weight lower than 10,000 g / mol, thereby improving processability and fluidity in the copper clad laminate (CCL) manufacturing process. In some embodiments, the first styrene copolymer may have a weight average molecular weight in the range of higher than or equal to 5,000 g / mol and lower than 10,000 g / mol. In some embodiments, the first styrene copolymer may have a weight average molecular weight in the range of 5,000 g / mol to 9,000 g / mol, 5,000 g / mol to 8,000 g / mol, 5,000 g / mol to 7,000 g / mol, or 5,000 g / mol to 6,000 g / mol. In some embodiments, the first styrenic copolymer may have a weight average molecular weight in a range of 5,000 g / mol to 8,000 g / mol.
[0038] In an embodiment where the first styrenic copolymer is liquid at 25°C and the second styrenic copolymer is solid at 25°C, the first styrenic copolymer may have a weight average molecular weight of less than 20,000 g / mol. In some embodiments, the first styrenic copolymer may have a weight average molecular weight of less than 10,000 g / mol, thereby improving processability and fluidity in the copper clad laminate (CCL) manufacturing process. In some embodiments, the first styrenic copolymer may have a weight average molecular weight in the range of greater than or equal to 5,000 g / mol and less than 10,000 g / mol. In some embodiments, the first styrenic copolymer may have a weight average molecular weight in the range of 5,000 g / mol to 9,000 g / mol, 5,000 g / mol to 8,000 g / mol, 5,000 g / mol to 7,000 g / mol, or 5,000 g / mol to 6,000 g / mol. In some embodiments, the first styrenic copolymer may have a weight average molecular weight in a range of 5,000 g / mol to 8,000 g / mol.
[0039] In some embodiments of the present invention, the first styrenic copolymer has a polydispersity index (PDI) in the range of 1.0 to 1.1, wherein the polydispersity index (PDI) is determined by gel permeation chromatography (GPC).
[0040] The first styrene copolymer may have a styrene block (as a hard segment) and a soft segment. The hard segment provides a higher glass transition temperature (glass transition temperature, Tg), and contributes to the strength, hardness and high temperature performance of the first styrene copolymer. The soft segment has some functional groups (such as vinyl) for curing, and contributes to the elasticity, toughness and resilience of the first styrene copolymer. In some embodiments, the first styrene copolymer may include 10 to 90 wt% of the hard segment and 90 to 10 wt% of the soft segment, based on the total weight of the first styrene copolymer being 100 wt%. Examples of soft segments are butadiene blocks and isoprene blocks, but the present invention is not limited thereto.
[0041] In the embodiment where the first styrene copolymer comprises a butadiene block and a styrene block as a soft segment, the weight ratio of the styrene block to the butadiene block may be 10:90 to 90:10. In some embodiments, the weight ratio of the styrene block to the butadiene block may be 10:90 to 80:20, 10:90 to 70:30, 10:90 to 60:40, or 10:90 to 50:50, but the present invention is not limited thereto. In some embodiments, the weight ratio of the styrene block to the butadiene block is 10:90 to 50:50. In the present invention, the weight ratio of the styrene block to the butadiene block is determined by proton nuclear magnetic resonance (PRNMR). 1 H-NMR) method.
[0042] The butadiene block may contain only the 1,2-bonded structure represented by the formula (1), or contain the 1,2-bonded structure represented by the formula (1) and the 1,4-bonded structure represented by the formula (2).
[0043]
[0044] In some embodiments, in the butadiene block, the molar ratio of the 1,2-bonded structure represented by formula (1) to the 1,4-bonded structure represented by formula (2) may be 50:50 to 100:0. In embodiments where the first styrene copolymer has a molar ratio of the 1,2-bonded structure represented by formula (1) to the 1,4-bonded structure represented by formula (2) in the above range, the first styrene copolymer has a high cure density. Therefore, the first styrene copolymer may have improved thermal properties. In some embodiments, in the butadiene block, the molar ratio of the 1,2-bonded structure represented by formula (1) to the 1,4-bonded structure represented by formula (2) may be 3:1 to 99:1. In some embodiments, in the butadiene block, the molar ratio of the 1,2-bonded structure represented by formula (1) to the 1,4-bonded structure represented by formula (2) may be 3:1 to 7:1, providing superior thermal properties. In some embodiments, the first styrene copolymer is a styrene-butadiene-styrene triblock copolymer (SBS), and in the butadiene block, the molar ratio of the 1,2-bonded structure represented by formula (1) to the 1,4-bonded structure represented by formula (2) may be 5:1 to 7:1. In the present invention, the molar ratio of formula (1) to formula (2) is determined by proton nuclear magnetic resonance ( 1 H-NMR) method.
[0045] The first styrene copolymer may be a styrene block copolymer or a styrene random copolymer. In some embodiments, the first styrene copolymer is a styrene block copolymer, wherein the styrene block copolymer has less than 50wt% of random comonomer repeating units based on the total weight of the first styrene copolymer being set to 100wt%, thereby providing superior electrical performance. In some embodiments, the first styrene copolymer may be a styrene block copolymer selected from the group consisting of styrene-butadiene block copolymer (SB), styrene-butadiene-styrene triblock copolymer (SBS), butadiene-styrene-butadiene triblock copolymer (BSB), and any combination thereof, but the present invention is not limited thereto. In some embodiments, the first styrene copolymer may be a styrene-butadiene-styrene triblock copolymer (SBS), or a styrene-butadiene diblock copolymer (SB). In some embodiments, the first styrene copolymer may be a styrene-butadiene-styrene triblock copolymer (SBS). In some embodiments, the first styrene copolymer may be a styrene-butadiene-styrene triblock copolymer (SBS) that is liquid at 25°C.
[0046] In some embodiments, in embodiments where the first styrenic copolymer is a styrene-butadiene-styrene triblock copolymer (SBS), in the butadiene block of the styrene-butadiene-styrene triblock copolymer (SBS), the molar ratio of the 1,2-bonded structure represented by formula (1) to the 1,4-bonded structure represented by formula (2) can be 3:1 to 7:1.
[0047] In some embodiments, the first styrene copolymer can be produced using the method described in Japanese Unexamined Patent Application Publication No. 1994-192502, Japanese Unexamined Patent Application Publication No. 2000-514122, or Japanese Unexamined Patent Application Publication No. 2007-302901, but the present invention is not limited thereto. In some embodiments, the first styrene copolymer can be produced through the first styrene copolymer preparation method. The preparation method of the first styrene copolymer may include the following steps: introducing a first styrene monomer and reacting the first styrene monomer to form a first styrene block; introducing a butadiene monomer and reacting the butadiene monomer to form a butadiene block bonded to the first styrene block; introducing a second styrene monomer as needed and reacting the second styrene monomer to form a second styrene block bonded to the butadiene block. In some embodiments, the preparation method of the first styrene copolymer may also include: before introducing the first styrene monomer, the second styrene monomer and the butadiene monomer, purifying them under an inert atmosphere. In some embodiments, the preparation method of the first styrene copolymer may also include a termination step after obtaining the first styrene copolymer having a desired weight average molecular weight.
[0048] The first styrene copolymer has high fluidity. Therefore, the processability of the polymer composite material comprising the first styrene copolymer can be improved. In addition, the short molecular chain of the first styrene copolymer can be used as a buffer during impact, thereby improving the toughening effect of the product made of the polymer composite material comprising the first styrene copolymer.
[0049] In the embodiment where the first styrenic copolymer has a weight average molecular weight lower than 20,000 g / mol and the second styrenic copolymer has a weight average molecular weight higher than 20,000 g / mol, the molecular weight of the second styrenic copolymer is measured by gel permeation chromatography (GPC). In certain embodiments, the second styrenic copolymer may have a weight average molecular weight higher than 20,000 g / mol and lower than 80,000 g / mol. In certain embodiments, the second styrenic copolymer may have a weight average molecular weight in the range of 40,000 g / mol to 78,000 g / mol, 40,000 g / mol to 60,000 g / mol, 40,000 g / mol to 70,000 g / mol or 40,000 g / mol to 50,000 g / mol. In certain embodiments, the second styrenic copolymer may have a weight average molecular weight in the range of 40,000 g / mol to 60,000 g / mol.
[0050] In the embodiment that the first styrenic copolymer is liquid at 25 ℃ and the second styrenic copolymer is solid at 25 ℃, the second styrenic copolymer can have a weight average molecular weight higher than 20,000g / mol. In some embodiments, the second styrenic copolymer can have a weight average molecular weight higher than 20,000g / mol and lower than 80,000g / mol. In some embodiments, the second styrenic copolymer can have a weight average molecular weight in the range of 40,000g / mol to 78,000g / mol, 40,000g / mol to 70,000g / mol, 40,000g / mol to 60,000g / mol or 40,000g / mol to 50,000g / mol. In some embodiments, the second styrenic copolymer can have a weight average molecular weight in the range of 40,000g / mol to 60,000g / mol.
[0051] The second styrenic copolymer may have a styrene block (as a hard segment) and a soft segment. The hard segment provides a higher glass transition temperature (Tg) and contributes to the strength, hardness and high temperature performance of the second styrenic copolymer. The soft segment has some functional groups (such as vinyl) for curing, and contributes to the elasticity, toughness and resilience of the second styrenic copolymer. In some embodiments, the second styrenic copolymer may include 10 to 90 wt% of the hard segment and 90 to 10 wt% of the soft segment, based on the total weight of the second styrenic copolymer being set to 100 wt%. Examples of soft segments are butadiene blocks and isoprene blocks, but the present invention is not limited thereto.
[0052] In embodiments where the second styrenic copolymer comprises a butadiene block as a soft segment and a styrene block as a hard segment, the weight ratio of the styrene block to the butadiene block may be 10:90 to 90:10. In some embodiments, the weight ratio of the styrene block to the butadiene block may be 10:90 to 80:20, 10:90 to 70:30, 10:90 to 60:40, 20:80 to 80:20, 30:70 to 80:20, or 40:60 to 80:20, but the present invention is not limited thereto. In some embodiments, the weight ratio of the styrene block to the butadiene block is 10:90 to 50:50. In the present invention, the weight ratio of the styrene block to the butadiene block is determined by proton nuclear magnetic resonance ( 1 H-NMR) method.
[0053] In embodiments where the second styrene-based copolymer includes a butadiene block as a soft segment, the butadiene block may include only the 1,2-bonded structure represented by formula (1) above, or include the 1,2-bonded structure represented by formula (1) and the 1,4-bonded structure represented by formula (2) above.
[0054] In some embodiments, in the butadiene block, the molar ratio of the 1,2-bonded structure represented by formula (1) to the 1,4-bonded structure represented by formula (2) may be 50:50 to 100:0. In embodiments where the second styrene copolymer has a molar ratio of the 1,2-bonded structure represented by formula (1) to the 1,4-bonded structure represented by formula (2) in the above range, the second styrene copolymer has a high cure density. Therefore, the second styrene copolymer may have improved thermal properties. In some embodiments, in the butadiene block, the molar ratio of the 1,2-bonded structure represented by formula (1) to the 1,4-bonded structure represented by formula (2) may be 80:20 to 99:1. In some embodiments, in the butadiene block, the molar ratio of the 1,2-bonded structure represented by formula (1) to the 1,4-bonded structure represented by formula (2) may be 5:1 to 7:1. In the present invention, the molar ratio of formula (1) to formula (2) is determined by proton nuclear magnetic resonance (1 H-NMR) method.
[0055] The second styrenic copolymer may be a styrenic block copolymer or a styrenic random copolymer. In some embodiments, the second styrenic copolymer is a styrenic block copolymer, wherein the styrenic block copolymer has less than 50wt% of random comonomer repeating units, based on the total weight of the second styrenic copolymer being set to 100wt%. In some embodiments, the second styrenic copolymer may be a styrenic block copolymer selected from the group consisting of styrene-butadiene block copolymer (SB), styrene-butadiene-styrene triblock copolymer (SBS), butadiene-styrene-butadiene triblock copolymer (BSB), and any combination thereof, but the present invention is not limited thereto. In some embodiments, the second styrenic copolymer may be a styrene-butadiene-styrene triblock copolymer (SBS) having a weight average molecular weight of less than 80,000 g / mol. In some embodiments, the second styrenic copolymer may be a styrene-butadiene-styrene triblock copolymer (SBS) that is solid at 25°C.
[0056] In some embodiments, the second styrene copolymer may have a viscosity in a range of greater than or equal to 54.4 Pa·s and less than 521.4 Pa·s. In some embodiments, the second styrene copolymer may have a viscosity in a range of 114.8 Pa·s to 327.4 Pa·s, thereby providing superior mechanical properties. The viscosity was measured by rheometer, and the measurement was performed according to the following method: a sample with a concentration of 35 wt% in methyl ethyl ketone (MEK) was prepared, and the shear rate parameter was set to 50 s at a temperature of 25°C. -1 The measurement was carried out under the conditions.
[0057] In some embodiments, the second styrenic copolymer may be produced using a method substantially similar to the method for producing the first styrenic copolymer, and thus will not be repeated herein.
[0058] The second styrene copolymer has high molecular entanglement. The second styrene copolymer can have desired thermal and physical properties. Therefore, the thermal and physical properties of the polymer composite material containing the second styrene copolymer can be improved.
[0059] The polymer composite material comprising above-mentioned first styrene copolymer and second styrene copolymer of the present invention can be combined with hydrocarbon resin, to provide the low dielectric resin composition with low dielectric loss tangent (Df).In certain embodiments, the weight ratio of the first styrene copolymer to the second styrene copolymer can be in the scope of 5 / 95 to 95 / 5,10 / 90 to 90 / 10,20 / 80 to 80 / 20 or 25 / 75 to 80 / 20.In certain embodiments, the weight ratio of the first styrene copolymer to the second styrene copolymer can be 5 / 95,10 / 90,15 / 85,20 / 80,25 / 75,30 / 70,35 / 65,40 / 60,45 / 55,50 / 50,55 / 45,60 / 40,65 / 35,70 / 30,75 / 25,80 / 20,85 / 15,90 / 10 or 95 / 5, but the present invention is not limited thereto. In some embodiments, the polymer composite material of the present invention can also improve the thermal properties and / or mechanical properties of the low dielectric resin composition comprising a hydrocarbon resin, and can prevent the embrittlement problem that exists when the hydrocarbon resin is used alone. Therefore, in some embodiments, the low dielectric resin composition comprising the polymer composite material of the present invention and a hydrocarbon resin can include good thermal properties and / or mechanical properties (high peel strength).
[0060] The polymer composite material of the present invention can be used to make a metal foil laminate having a dielectric loss tangent (Df) less than or equal to 0.00200. In particular, the polymer composite material of the present invention can be combined with a hydrocarbon resin to provide a low dielectric resin composition with a low dielectric loss tangent (Df), which can be used to make a metal foil laminate. In some embodiments, the metal foil laminate includes a glass fiber cloth having a dielectric loss tangent (Df) less than or equal to 0.0030.
[0061] One embodiment of the present invention provides a low dielectric resin composition. In some embodiments, the low dielectric resin composition may include the aforementioned polymer composite material and a poly(arylene ether) compound. In some embodiments, the low dielectric resin composition does not contain a poly(arylene ether) compound. In the present invention, the poly(arylene ether) compound may be a polymer comprising a plurality of units represented by the following formula (3):
[0062]
[0063] Among them, for each structural unit, each R 3 are independently hydrogen or C 1-4 Alkyl, and "*" indicates the connection point to other groups.
[0064] The low dielectric resin composition of the present invention comprises a hydrocarbon resin, a first styrene copolymer, and a second styrene copolymer. In some embodiments, the first styrene copolymer has a weight average molecular weight of less than 20,000 g / mol, and the second styrene copolymer has a weight average molecular weight of more than 20,000 g / mol, but the present invention is not limited thereto. In some embodiments, the first styrene copolymer is liquid at 25° C., and the second styrene copolymer is solid at 25° C. In some embodiments, the hydrocarbon resin, the first styrene copolymer, and the second styrene copolymer can be separated from each other by common purification methods.
[0065] In some embodiments, the low dielectric resin composition comprises greater than 53 wt% hydrocarbon resin based on the total weight of the low dielectric resin composition. In some embodiments, the low dielectric resin composition comprises greater than 57 wt% hydrocarbon resin based on the total weight of the low dielectric resin composition. In some embodiments, the low dielectric resin composition comprises greater than 54 wt%, 55 wt%, 56 wt%, 57 wt%, 58 wt%, 59 wt%, 60 wt%, 61 wt%, or 62 wt% hydrocarbon resin based on the total weight of the low dielectric resin composition.
[0066] In some embodiments, based on 100 parts by weight of hydrocarbon resin, the low dielectric resin composition may include 1 to 50 parts by weight of the first styrene copolymer, and 1 to 50 parts by weight of the second styrene copolymer. In some embodiments, based on 100 parts by weight of hydrocarbon resin, the low dielectric resin composition may include 1 to less than 50 parts by weight of the first styrene copolymer, and 1 to less than 50 parts by weight of the second styrene copolymer. In some embodiments, based on 100 parts by weight of hydrocarbon resin, the low dielectric resin composition may include 4 to 40 parts by weight of the first styrene copolymer, and 2 to 20 parts by weight of the second styrene copolymer. In some embodiments, based on 100 parts by weight of hydrocarbon resin, the low dielectric resin composition may include 4 to 20 parts by weight of the first styrene copolymer, and 2 to 17 parts by weight of the second styrene copolymer.
[0067] The weight ratio of the hydrocarbon resin to the sum of the first styrene copolymer and the second styrene copolymer is in the range of greater than 100 / 50 and less than or equal to 100 / 10. The weight ratio of the hydrocarbon resin to the sum of the first styrene copolymer and the second styrene copolymer is in the range of greater than 100 / 35 and less than or equal to 100 / 10. In embodiments where the weight ratio of the hydrocarbon resin to the sum of the first styrene copolymer and the second styrene copolymer is in the above range, the low dielectric resin composition exhibits mechanical strength (peel strength). In some embodiments, the weight ratio of the hydrocarbon resin to the sum of the first styrene copolymer and the second styrene copolymer may be 100 / 45 to 100 / 10, 100 / 40 to 100 / 15, 100 / 35 to 100 / 20, or 100 / 34 to 100 / 20. In some embodiments, the weight ratio of the hydrocarbon resin to the sum of the first styrene copolymer and the second styrene copolymer may be 100 / 21.
[0068] The weight ratio of the first styrenic copolymer to the second styrenic copolymer may range from 5 / 95 to 95 / 5, 10 / 90 to 90 / 10, 20 / 80 to 80 / 20, or 25 / 75 to 80 / 20. In some embodiments, the weight ratio of the first styrenic copolymer to the second styrenic copolymer may be 5 / 95, 10 / 90, 15 / 85, 20 / 80, 25 / 75, 30 / 70, 35 / 65, 40 / 60, 45 / 55, 50 / 50, 55 / 45, 60 / 40, 65 / 35, 70 / 30, 75 / 25, 80 / 20, 85 / 15, 90 / 10, or 95 / 5, but the present invention is not limited thereto.
[0069] The first styrene copolymer and the second styrene copolymer included in the low dielectric resin composition are substantially similar to the first styrene copolymer and the second styrene copolymer included in the above polymer composite material, and thus will not be repeated here.
[0070] The hydrocarbon resin included in the low dielectric resin composition may include repeating units (A) derived from a bridged ring monomer compound, repeating units (B) derived from a monovinyl aromatic compound, and repeating units (C) derived from a divinyl aromatic compound. In some embodiments, based on 100 mol% of the total units in the hydrocarbon resin, the hydrocarbon resin may include: 0 to 40 mol% of repeating units (A) derived from a bridged ring monomer compound, 15 to 92 mol% of repeating units (B) derived from a monovinyl aromatic compound, and 8 to 80 mol% of repeating units (C) derived from a divinyl aromatic compound.
[0071] Here, the "bridged ring monomer compound" in the present invention refers to a compound that includes a bridged ring structure and can be polymerized with other identical or different compounds to form a polymer. The bridged ring structure refers to a structure that includes at least two carbon rings, and the at least two carbon rings share two carbon atoms that are not directly connected. In some embodiments, the bridged ring structure in the bridged ring monomer compound may contain 3 to 12 ring atoms and 1 to 2 double bonds. In some embodiments, the bridged ring structure may be unsubstituted. In some embodiments, at least one hydrogen atom on the bridged ring structure may be selected from C 1-20 Alkyl, C 2-20 Alkenyl, and having C 1-20 In some embodiments, the bridge ring structure may have at least two substituents, and the at least two substituents may be selected from C 1-20 Alkyl, C 2-20 Alkenyl, and having C 1-20 Any two substituents in the group consisting of carboxylate groups of alkane chains. Adjacent substituents in the at least two substituents may form a ring together. Examples of bridged ring monomer compounds include, but are not limited to, norbornene (NB), dicyclopentadiene (DCPD), dicycloheptadiene (NBD), 5-acetyl-2-norbornene, methyl 5-norbornene-2-carboxylate, vinyl norbornene, ethylidene-norbornene, or a combination thereof.
[0072]
[0073]
[0074] The repeating unit (A) derived from the bridged ring monomer compound comprises a bridged ring structure from the bridged ring monomer compound. Therefore, the repeating unit (A) may comprise a bridged ring structure having 3 to 12 ring atoms and 0 to 1 double bonds. In some embodiments, the repeating unit (A) may have the following structure, but the present invention is not limited thereto:
[0075]
[0076]
[0077] The "*" in the above structure indicates a connection site connected to other groups. Compared with linear repeating units, repeating units (A) having a bridged ring structure have higher rigidity, and thus can increase the glass transition temperature of hydrocarbon resins or enhance the thermal properties of hydrocarbon resins. When the content of repeating units (A) in hydrocarbon resins is too high, for example, when it is higher than 40 mol%, the cost-effectiveness of hydrocarbon resins will be reduced. In some embodiments, the hydrocarbon resin of the present invention may contain 0 to 38 mol%, 0 to 30 mol%, 0 to 25 mol%, 0 to 20 mol%, 20 to 40 mol%, 20 to 38 mol%, 20 to 30 mol%, or 20 to 25 mol% of repeating units (A). In some embodiments, the hydrocarbon resin of the present invention may contain 3 mol%, 5 mol%, 7 mol%, 9 mol%, 10 mol%, 20 mol%, 22 mol%, 25 mol%, 30 mol%, 32 mol%, 35 mol%, or 38 mol% of repeating units (A).
[0078] Here, the "monovinyl aromatic compound" in the present invention refers to a compound including a carbocyclic aromatic structure, wherein one hydrogen atom on a ring-forming carbon atom of the carbocyclic aromatic structure is replaced by a vinyl group. In some embodiments, the vinyl group may be unsubstituted. In some embodiments, at least one hydrogen atom on the vinyl group may be replaced by a C 1-20 In some embodiments, the carbocyclic aromatic structure may contain 6 to 60 or 6 to 20 ring-forming carbon atoms. In some embodiments, the carbocyclic aromatic structure may be unsubstituted. In some embodiments, at least one hydrogen on the ring-forming carbon atom in the carbocyclic aromatic structure may be replaced by a C 1-20 Examples of monovinyl aromatic compounds include, but are not limited to, styrene, methylstyrene, ethylstyrene (EVB), or any combination thereof.
[0079] The repeating unit (B) derived from a monovinyl aromatic compound comprises a carbocyclic aromatic structure derived from a monovinyl aromatic compound. For example, in some embodiments, the repeating unit (B) may have the following structure, but the present invention is not limited thereto:
[0080] The "*" in the above structure indicates a linking site to other groups.
[0081] The repeating unit (B) can increase the solubility of the hydrocarbon resin in solvents such as toluene. When the content of the repeating unit (B) in the hydrocarbon resin is too low, for example, less than 15 mol%, the solubility of the hydrocarbon resin in the solvent is poor. When the content of the repeating unit (B) in the hydrocarbon resin is too high, for example, greater than 92 mol%, other properties of the hydrocarbon resin, such as its thermal properties, may be reduced. In some embodiments, the hydrocarbon resin of the present invention may contain 15 to 92 mol% of the repeating unit (B). In some embodiments, the hydrocarbon resin of the present invention may contain 20 to 92 mol%, 20 to 90 mol%, 25 to 85 mol%, 30 to 80 mol%, 35 to 80 mol%, 40 to 80 mol%, or 45 to 80 mol% of the repeating unit (B). In some embodiments, the hydrocarbon resin of the present invention may contain 46 mol%, 48 mol%, 50 mol%, 55 mol%, 60 mol%, 67 mol%, 72 mol%, 76 mol%, or 78 mol% of the repeating unit (B).
[0082] Here, the "bisvinyl aromatic compound" in the present invention refers to a compound comprising a carbocyclic aromatic structure, wherein two hydrogen atoms on the ring carbon atoms of the carbocyclic aromatic structure are replaced by vinyl atoms. In some embodiments, the vinyl atoms may be unsubstituted. In some embodiments, at least one hydrogen atom on the vinyl atoms may be replaced by C 1-20 In some embodiments, the carbocyclic aromatic structure may contain 6 to 60 or 6 to 20 ring-forming carbon atoms. In some embodiments, the carbocyclic aromatic structure may be unsubstituted. In some embodiments, at least one hydrogen on the ring-forming carbon atom of the carbocyclic aromatic structure may be replaced by a C 1-20 Examples of divinyl aromatic compounds include, but are not limited to, divinylbenzene (DVB), diisopropenylbenzene, or any combination thereof.
[0083] The repeating unit (C) derived from the divinyl aromatic compound comprises a carbocyclic aromatic structure from the divinyl aromatic compound. In some embodiments, the repeating unit (C) may comprise a cross-linking unit and a non-cross-linking unit. In some embodiments, the repeating unit (C) may comprise a cross-linking unit as shown below:
[0084] However, the present invention is not limited thereto. In some embodiments, the repeating unit (C) may include a non-crosslinking unit as shown below, but the present invention is not limited thereto: The "*" in the above structure indicates a linking site to other groups.
[0085] The degree of crosslinking of the repeating unit (C) was determined by using the samples prepared in CDCl313 C-NMR (Nuclear Magnetic Resonance, NMR) and 1 H-NMR measurement; and the degree of crosslinking is calculated by the following formula:
[0086]
[0087] In some embodiments, the degree of crosslinking of the repeating unit (C) is 0.2 to 0.6. The degree of crosslinking in the range helps to achieve excellent thermal and electrical properties without causing processability issues. The higher the degree of crosslinking of the hydrocarbon resin, the better the thermal properties, thermal stability, and / or electrical properties of the hydrocarbon resin composition, but when the degree of crosslinking is higher than 0.6, the processability of the hydrocarbon resin will decrease. In some embodiments, the degree of crosslinking of the repeating unit (C) may be 0.2 to 0.5. In some embodiments, the degree of crosslinking of the repeating unit (C) may be 0.3, 0.35, 0.4, or 0.45, but the present invention is not limited thereto.
[0088] The repeating unit (C) can increase the crosslinking degree of the hydrocarbon resin. The higher the crosslinking degree of the hydrocarbon resin, the better the thermal properties, thermal stability, and / or electrical properties of the hydrocarbon resin. When the content of the repeating unit (C) in the hydrocarbon resin is too low, for example, less than 8 mol%, the crosslinking degree of the hydrocarbon resin is low, and the thermal properties and / or electrical properties of the hydrocarbon resin are poor. When the content of the repeating unit (C) in the hydrocarbon resin is too high, for example, greater than 80 mol%, the processability of the hydrocarbon resin will decrease. In some embodiments, the hydrocarbon resin of the present invention may contain 8 to 80 mol%, 8 to 70 mol%, 8 to 60 mol%, 8 to 50 mol%, 8 to 45 mol%, 8 to 40 mol%, or 8 to 35 mol% of the repeating unit (C). In some embodiments, the hydrocarbon resin of the present invention may contain 8 mol%, 9 mol%, 10 mol%, 11 mol%, 12 mol%, 16 mol%, 20 mol%, 30 mol%, 32 mol%, 35 mol%, 40 mol%, or 45 mol% of the repeating unit (C). In some embodiments, the sum of the repeating unit (A) and the repeating unit (C) is greater than or equal to 8 mol%. In some embodiments, the sum of the repeating unit (A) and the repeating unit (C) is greater than or equal to 13 mol%, or even greater than or equal to 15 mol%. As described above, both the repeating unit (A) and the repeating unit (C) affect the thermal properties and thermal stability of the hydrocarbon resin. The inventors have found that the sum of the repeating unit (A) and the repeating unit (C) is greater than or equal to 8 mol%, which can provide the hydrocarbon resin with excellent thermal properties and thermal stability.
[0089] In some embodiments, the hydrocarbon resin may contain reactive double bonds. In the present invention, "reactive double bonds" refer to double bonds in repeating unit (A) or repeating unit (C) that can react with other compounds or polymers. For example, in some embodiments, the reactive double bonds include the double bonds in repeating unit (A) shown below: And the double bonds on the non-benzene rings in the repeating unit (C) are shown below: However, the present invention is not limited thereto.
[0090] In some embodiments, the content of hydrogen atoms in the reactive double bonds of the hydrocarbon resin is less than 10%. When the content of hydrogen atoms in the reactive double bonds of the hydrocarbon resin is too high, for example, when it is higher than 10%, the hydrocarbon resin is easily oxidized during the heating process, resulting in poor electrical properties of the hydrocarbon resin. In some embodiments, the content of hydrogen atoms in the reactive double bonds of the hydrocarbon resin is greater than 2.2%. In some embodiments, the content of hydrogen atoms in the reactive double bonds of the hydrocarbon resin is in a range of greater than 2.2% and less than 10%. In some embodiments, the content of hydrogen atoms in the reactive double bonds of the hydrocarbon resin is in a range of greater than or equal to 2.3% and less than 6.6%. When the content of hydrogen atoms in the reactive double bonds of the hydrocarbon resin is too low, for example, when it is lower than 2.2%, the peel strength of the layer containing the hydrocarbon resin is too low. In some embodiments, the content of hydrogen atoms in the reactive double bonds of the hydrocarbon resin may be 2.3% to 10%, 2.3% to 9%, 2.3% to 7%, 2.3% to 6%, or 2.3% to 4%. When the content of hydrogen atoms in the reactive double bonds of the hydrocarbon resin is within the above range, the hydrocarbon resin is not easily oxidized under high temperature conditions (e.g., above 150°C) and tends to complete the cross-linking reaction before being oxidized. Therefore, the electrical performance of the hydrocarbon resin can be improved. In some embodiments, the number average molecular weight (Mn) of the hydrocarbon resin can be 2,500 to 13,000 g / mol, which is determined by gel permeation chromatography (GPC). When the number average molecular weight of the hydrocarbon resin is too high, the solubility of the hydrocarbon resin will decrease.
[0091] The hydrocarbon resin of the present invention having the above characteristics has good thermal properties, thermal stability, and / or electrical performance. For example, in some embodiments, the hydrocarbon resin of the present invention has a glass transition temperature greater than about 100°C, a dielectric constant (Dk) less than about 3.4, a dielectric loss tangent (Df) less than about 0.0030, a small difference in dielectric constant and / or dielectric loss tangent before and after the heating process, and / or a dielectric loss tangent less than about 0.0020 after the heating process. The Dk / Df of the hydrocarbon resin is analyzed by the following method, including: dissolving 20g of the resin in 20g of toluene to form a mixture; immersing a glass fiber cloth in the mixture for 16 hours to form a sample; and measuring the Dk / Df of the sample at 28GHz using a network analyzer software (network analyzerKeysight, P5007A, SCR). Furthermore, the glass transition temperature of the hydrocarbon resin of the present invention is measured using dynamic mechanical analysis (DMA, TA / Q800). In addition, the hydrocarbon resin of the present invention also has good solubility and / or processability. Therefore, the hydrocarbon resin of the present invention can be easily dissolved in a solvent to form a resin composition with good thermal properties, thermal stability, electrical performance and / or processability.
[0092] In some embodiments, the low dielectric resin composition may further include an additive to modify the performance of the low dielectric resin composition. In some embodiments, the low dielectric resin composition may include 1 to 50 parts by weight of the additive, based on the sum of the hydrocarbon resin, the first styrene copolymer, and the second styrene copolymer being 100 parts by weight. The additive may be selected from the group consisting of an initiator, a flame retardant, an inorganic filler, a crosslinking aid, and any combination thereof. In the present invention, the initiator, the flame retardant, the inorganic filler, and the crosslinking aid are not particularly limited.
[0093] Examples of the initiator include benzoyl peroxide, cumene hydroperoxide, 2,5-dimethylhexane-2,5-dihydroperoxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexine-3, di-t-butyl peroxide, t-butylcumyl peroxide, α,α'-bis(t-butylperoxy-m-isopropyl)benzene, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, dicumyl peroxide, peroxide), di-t-butyl peroxyisophthalate, t-butylperoxybenzoate, 2,2-bis(t-butylperoxy)butane, 2,2-bis(t-butylperoxy)octane, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, di(trimethylsilyl)peroxide, trimethylsilyltriphenylsilyl peroxide, or any combination thereof, but the present invention is not limited thereto. In some embodiments, the initiator is a peroxide-type compound. In some embodiments, the low dielectric resin composition may include 1 to 10 parts by weight of the initiator based on 100 parts by weight of the sum of the hydrocarbon resin, the first styrene-based copolymer, and the second styrene-based copolymer, but the present invention is not limited thereto.
[0094] Examples of flame retardants include halogen-based flame retardants (e.g., bromine-based flame retardants), phosphorus-based flame retardants, other suitable flame retardants, or any combination thereof, but the present invention is not limited thereto. Examples of phosphorus-containing flame retardants include phosphates (e.g., condensed phosphates and cyclic phosphates), phosphazene compounds (e.g., cyclic phosphazene compounds), phosphinate-based flame retardants (e.g., aluminum dialkyl phosphinate), melamine-based flame retardants (e.g., melamine phosphate and melamine polyphosphate), other suitable flame retardants, or any combination thereof, but the present invention is not limited thereto. In some embodiments, the low dielectric resin composition may include 1 to 20 parts by weight of a phosphorus-containing flame retardant, based on the sum of the hydrocarbon resin, the first styrene copolymer, and the second styrene copolymer, but the present invention is not limited thereto.
[0095] In some embodiments of the present invention, examples of inorganic fillers may include silicon dioxide, aluminum oxide, talc, aluminum hydroxide, magnesium hydroxide, titanium oxide, mica, aluminum borate, barium sulfate, calcium carbonate, other suitable materials, or any combination thereof, but the present invention is not limited thereto. In some embodiments, the inorganic filler is silicon dioxide. In some embodiments, the low dielectric resin composition may include 10 to 50 parts by weight of the inorganic filler, based on the sum of the hydrocarbon resin, the first styrene copolymer, and the second styrene copolymer being 100 parts by weight, but the present invention is not limited thereto.
[0096] Crosslinking aids can enhance the thermal properties of low dielectric resin compositions. Examples of crosslinking aids include triallyl cyanurate (TAC), triallyl isocyanurate (TAIC), trimethallyl isocyanurate (TMAIC), diallyl phthalate, divinylbenzene, 1,2,4-triallyl trimellitate, or any combination thereof, but the present invention is not limited thereto. In some embodiments, the low dielectric resin composition includes a crosslinking aid and an initiator, wherein the initiator is a peroxide-type compound. In some embodiments, the crosslinking aid is divinylbenzene, triallyl isocyanurate (TAIC), or a combination thereof, but the present invention is not limited thereto. In some embodiments, the crosslinking aid is divinylbenzene. In some embodiments, the low dielectric resin composition may include 1 to 50 parts by weight of the crosslinking agent based on 100 parts by weight of the total of the hydrocarbon resin, the first styrene-based copolymer, and the second styrene-based copolymer, but the present invention is not limited thereto.
[0097] The production method of the low dielectric resin composition of the present invention is not particularly limited. In some embodiments, the low dielectric resin composition is prepared by batch mixing the hydrocarbon resin, the first styrene copolymer, the second styrene copolymer, and optional additives with an organic solvent. In some embodiments, the organic solvent may include methyl ethyl ketone, toluene, or a combination thereof, but the present invention is not limited thereto.
[0098] The mixing process can be performed simultaneously or sequentially, but the present invention is not limited thereto. In some embodiments, the mixing process can be performed using a suitable mixer selected according to the amount of low dielectric resin composition to be prepared, but the present invention is not limited thereto. In some embodiments, the mixing process is performed at room temperature and is not completed until the hydrocarbon resin, the first styrene copolymer, the second styrene copolymer, and the optional additives are completely dispersed.
[0099] The low dielectric resin composition of the present invention has a dielectric loss tangent (Df) of less than or equal to 0.00200. The low dielectric resin composition of the present invention can be used to manufacture a metal foil laminate having a dielectric loss tangent (Df) of less than or equal to 0.00200.
[0100] One embodiment of the present invention provides a prepreg made from the above-mentioned low dielectric resin composition. That is, one embodiment of the present invention provides a prepreg made from a low dielectric resin composition, wherein the low dielectric resin composition comprises a hydrocarbon resin and a polymer composite material containing the above-mentioned first styrene copolymer and the second styrene copolymer. In some embodiments, the weight ratio of the first styrene copolymer to the second styrene copolymer is 5 / 95 to 95 / 5. In some embodiments, the first styrene copolymer has a weight average molecular weight of less than 20,000 g / mol, and the second styrene copolymer has a weight average molecular weight greater than 20,000 g / mol, but the present invention is not limited thereto. In some embodiments, the first styrene copolymer is liquid at 25°C, and the second styrene copolymer is solid at 25°C.
[0101] The method for preparing the prepreg is not particularly limited. In some embodiments, the prepreg is prepared from a mixture of a fiber substrate and the above-mentioned low dielectric resin composition, or a resin varnish containing the above-mentioned low dielectric resin composition. In some embodiments, the prepreg is prepared by a prepreg preparation method. The prepreg preparation method comprises: providing a resin varnish containing the above-mentioned low dielectric resin composition; immersing the fiber substrate in the resin varnish to form a mixture; and heating the mixture to 100-180°C to remove the solvent, thereby obtaining a prepreg in a semi-cured state.
[0102] In some embodiments, the resin varnish is prepared by a resin varnish preparation method. The resin varnish preparation method comprises a dissolving step and a dispersing step. In some embodiments, the dissolving step comprises dissolving the hydrocarbon resin, the first styrene copolymer, the second styrene copolymer, and an optional additive soluble in an organic solvent until they are completely dispersed. In some embodiments, the dispersing step comprises adding an optional additive insoluble in an organic solvent (e.g., an inorganic filler), and using a ball mill, a bead mill, a planetary mixer, a roller mill, other suitable devices, or any combination thereof to disperse it until a predetermined dispersion state is reached.
[0103] Examples of fiber substrates include glass fiber cloth, aramid cloth, polyester cloth, glass fiber non-woven fabric, aramid non-woven fabric, polyester non-woven fabric, pulp paper, printer paper, other suitable materials, or any combination thereof, but the present invention is not limited thereto. In some embodiments, the fiber substrate is glass fiber cloth having a dielectric loss tangent (Df) less than or equal to 0.0030.
[0104] The prepreg of the present invention having a dielectric loss tangent (Df) of less than or equal to 0.00200 can be used to prepare a metal foil laminate having a dielectric loss tangent (Df) of less than or equal to 0.00200.
[0105] One embodiment of the present invention provides a metal foil laminate comprising the above-mentioned prepreg. In some embodiments, a metal foil laminate having a dielectric loss tangent (Df) less than or equal to 0.00200 is manufactured using the aforementioned polymer composite material to form a mixture comprising a hydrocarbon resin. In some embodiments, the metal foil laminate has a structure in which a metal foil is stacked on top of a prepreg or a prepreg stack layer, and the stack structure is integrally laminated through hot pressing to obtain a double-sided metal-clad laminate or a single-sided metal-clad laminate. In some embodiments, the hot pressing conditions for complete curing can be appropriately set according to the thickness of the metal foil laminate to be produced, the type of hydrocarbon resin composition used for the prepreg, etc. For example, the hot pressing conditions can be set to a temperature of 170 to 220°C, a pressure of 1.0 to 4.0 MPa, and a time of 60 to 180 minutes.
[0106] Figure 1 FIG. 1 is a schematic diagram of a metal foil laminate 10 according to an embodiment of the present invention. Figure 1 As shown, the metal foil laminate 10 comprises a substrate 101, a polymer layer 103 disposed on the substrate 101, and an adhesive layer 105 disposed between the substrate 101 and the polymer layer 103. The adhesive layer 105 connects the substrate 101 and the polymer layer 103. The polymer layer 103 may comprise the above-mentioned prepreg. The metal foil laminate comprising the above-mentioned prepreg may have a dielectric loss tangent (Df) less than or equal to 0.00200. In some embodiments, the metal foil laminate comprising the above-mentioned prepreg may have excellent thermal properties, thermal stability, mechanical properties (high peel strength) and / or reliability.
[0107] In some embodiments, the substrate 101 may include a metal layer. In some embodiments, the substrate 101 may include a copper foil. In some embodiments, the adhesive layer 105 may include any material capable of connecting the substrate 101 and the polymer layer 103. In some embodiments, the adhesive layer 105 may include a silane adhesive.
[0108] One or more embodiments of the present invention will now be described in detail with reference to the following experimental examples. However, these experimental examples are only used to illustrate the embodiments of the present invention and are not intended to limit the scope of the embodiments of the present invention.
[0109] [Preparation of hydrocarbon resins HC 1 to 5]
[0110] According to the ratio shown in Table 1 below, a bridged ring monomer compound, a monovinyl aromatic compound, and a divinyl aromatic compound and toluene are added to a double-necked bottle to form a mixture. A catalyst shown in Table 1 is added to the mixture. The mixture is stirred for 3 hours at the reaction temperature shown in Table 1 below to polymerize the bridged ring monomer compound, the monovinyl aromatic compound, and the divinyl aromatic compound. Ammonium hydroxide (NH4OH) is added to the double-necked bottle to terminate the polymerization reaction. The polymer solution obtained from the polymerization reaction is dropped into isopropanol to obtain a white solid. The white solid is filtered and vacuum dried to obtain hydrocarbon resins HC 1-5.
[0111] [Measurement of the content of hydrogen atoms in reactive double bonds]
[0112] Hydrocarbon resins HC 1 to 5 were dissolved in deuterated chloroform (CDCl3). The hydrogen atom content in the reactive double bonds of the hydrocarbon resins HC 1 to 5 was measured by NMR (JEOL, JNM-ECZ400S / L1). Specifically, the hydrogen atom content in the reactive double bonds was calculated by dividing the sum of the integral values of the number of hydrogen atoms in the reactive double bonds by the sum of the integral values of all hydrogen atoms in the hydrocarbon resins HC 1 to 5.
[0113] [Measurement of number average molecular weight (Mn) and polymer dispersity index (PDI)]
[0114] The number average molecular weight and polymer dispersibility index (PDI) of hydrocarbon resins HC 1 to 5 were measured by gel permeation chromatography (GPC) (Waters APC, column: Waters Acquity XT 900) using polystyrene as a standard.
[0115] 5 mL of tetrahydrofuran (THF) was added to 0.01 g of hydrocarbon resin HC 1 to 5 to obtain samples of hydrocarbon resin HC 1 to 5. The samples of hydrocarbon resin HC 1 to 5 were filtered with a 0.22 μm filter and analyzed by an instrument to obtain the number average molecular weight (Mn) and polymer dispersibility index (PDI) of hydrocarbon resin HC 1 to 5. The property measurement results of hydrocarbon resin HC 1 to 5 are shown in the following Table 1.
[0116] Table 1
[0117]
[0118] *Mol % in Table 1 represents molar percentage.
[0119] [Preparation of Experimental Examples E1 to E13 and Comparative Examples C1 and C2]
[0120] Material
[0121] Hydrocarbon resin: the above-mentioned hydrocarbon resin HC 1 to 5.
[0122] The first styrene copolymer
[0123] Ricon-100: Styrene-butadiene random copolymer (SBR) manufactured by Cray Valley. Ricon-100 has a number average molecular weight of 4,500 Da, a viscosity of 40,000 cps at 45°C, a styrene content of 17-27 wt%, a 1,2-vinyl content of 70 wt%, a Tg of -22°C, and a specific gravity of 0.92 g / cm at 25°C. 3 .
[0124] SBS-L: a styrene-butadiene-styrene triblock copolymer (SBS) having a weight average molecular weight of 6,000 Da and a PDI of 1.04. The molar ratio of 1,2-bonded structure to 1,4-bonded structure in the butadiene block of SBS-L is 5:1 to 7:1, and the weight ratio of styrene block to butadiene block is 10:90 to 50:50.
[0125] Second styrene copolymer
[0126] SBS-1: a styrene-butadiene-styrene triblock copolymer (SBS) with a weight average molecular weight of 80,000 Da and a viscosity of 521.4 Pa·s. The molar ratio of 1,2-bonded structure to 1,4-bonded structure in the butadiene block of SBS-1 is 5:1 to 7:1, and the weight ratio of styrene block to butadiene block is 50:50.
[0127] SBS-2: a styrene-butadiene-styrene triblock copolymer (SBS) with a weight average molecular weight of 40,000 Da and a viscosity of 114.8 Pa·s. The molar ratio of 1,2-bonded structure to 1,4-bonded structure in the butadiene block of SBS-2 is 5:1 to 7:1, and the weight ratio of styrene block to butadiene block is 50:50.
[0128] Cross-linking aid: divinylbenzene compound, manufactured by Deltech, trade name "DVB".
[0129] Initiator: α,α'-bis(tert-butylperoxy)diisopropylbenzene compound, manufactured by NOF, trade name
[0130] "PERBUTYL P".
[0131] Additives - Inorganic filler: Silica filler, manufactured by Admatch, trade name "SS-10".
[0132] Preparation of metal foil laminates of Experimental Examples E1 to E13 and Comparative Examples C1 and C2 and measurement of their Dk / Df
[0133] The above materials were mixed with 50 to 60 parts by weight of toluene in the proportions shown in Tables 2 to 7 below to form the resin varnishes of Experimental Examples E1 to E13 and Comparative Examples C1 and C2. The abbreviation phr means "parts per hundred parts of resin". Two pieces of glass fiber cloth (Asahi 2116, Dk / Df=3.3 / 0.0030 at 10 GHz) were immersed in the resin varnishes of Experimental Examples E1 to E13 and Comparative Examples C1 and C2, respectively, and baked at 160 to 170°C for 5 to 15 minutes to form two polymer layers of Experimental Examples E1 to E13 and Comparative Examples C1 and C2. Then, high temperature elongation copper foil was placed between the two polymer layers of Experimental Examples E1 to E13 and Comparative Examples C1 and C2, respectively. The high temperature elongated copper foil was laminated with the two polymer layers of Experimental Examples E1 to E13 and Comparative Examples C1 and C2 at a pressure of 400 psi and a temperature of 210° C. for 1 hour to obtain metal foil laminates of Experimental Examples E1 to E13 and Comparative Examples C1 and C2, respectively.
[0134] The Dk / Df of the metal foil laminates of Experimental Examples E1 to E13 and Comparative Examples C1 and C2 at 10 GHz were measured using network analyzer software (network analyzer Keysight, P5007A, SCR). The results are shown in Tables 2 to 7 below.
[0135] Table 2
[0136]
[0137]
[0138] Table 3
[0139]
[0140] Table 4
[0141]
[0142]
[0143] Table 5
[0144]
[0145] Table 6
[0146]
[0147] Table 7
[0148]
[0149] [Peel strength test]
[0150] Four glass fiber cloths (Asahi 2116, Dk / Df=3.3 / 0.0030 at 10 GHz) were immersed in the resin varnish of Experimental Examples E7 to E13 and Comparative Examples C1 and C2, and baked at 160°C for 10 minutes to form four polymer layers of Experimental Examples E7 to E13 and Comparative Examples C1 and C2, respectively. The four polymer layers were laminated with copper foil layers. The copper foil layers were placed between the four polymer layers. The copper foil layers were pressed with the polymer layers to form the laminated structures of Experimental Examples E7 to E13 and Comparative Examples C1 and C2, respectively.
[0151] The peel strength of the laminated structures of Experimental Examples E7 to E13 and Comparative Examples C1 and C2 was measured using a tensile tester (SHIMADZU AG-Xplus, test conditions: test speed 50.8 mm / min, test length: 20 mm). The results are shown in Table 8 below.
[0152] [Measurement of glass transition temperature (Tg)]
[0153] Two glass fiber cloths (Asahi 2116, Dk / Df=3.3 / 0.0030 at 10 GHz) were immersed in the resin varnish of Experimental Examples E7 to E13 and Comparative Examples C1 and C2, and baked at 160 to 170°C for 5 to 15 minutes to form two polymer layers of Experimental Examples E7 to E13 and Comparative Examples C1 and C2, respectively. The two polymer layers were laminated with copper foil. The copper foil was placed between the two polymer layers. The copper foil and the polymer layer were pressed together to form the laminated boards of Experimental Examples E7 to E13 and Comparative Examples C1 and C2, respectively.
[0154] The glass transition temperature (Tg) of the laminates of Experimental Examples E7-E13 and Comparative Examples C1 and C2 was measured by dynamic mechanical analysis (DMA, TA / Q800) using a test frequency of 1 Hz and under the following test conditions: heating from 25°C to 270°C and a heating rate of 3°C / min. The glass transition temperature (Tg) was obtained from the tan Delta peak in the DMA chart, and the results are shown in Table 8 below.
[0155] Table 8
[0156] Peel Strength (lbf / in) Glass transition temperature(℃) Experimental Example E7 2.6 147.8 Experimental Example E8 2.7 144.4 Experimental Example E9 2.5 143.1 Experimental Example E10 1.61 147.2 Experimental Example E11 2.0 147.1 Experimental Example E12 2.7 144.4 Experimental Example E13 1.6 143.3 Comparative Example C1 Unable to measure Unable to measure Comparative Example C2 1.9 145.5
[0157] It can be seen from the above results that Comparative Example C1 cannot provide measurable results due to the impregnation processability problem during the prepreg preparation process.
[0158] As can be seen from Tables 2 to 7, after baking at 160°C, the dielectric loss tangent (Df) of the metal foil laminates of Experimental Examples E1 to E13 is lower than the dielectric loss tangent (Df) of the metal foil laminate of Comparative Example C2, and the dielectric loss tangent (Df) of the metal foil laminates of Experimental Examples E1 to E13 is less than or equal to 0.0020. In other words, the metal foil laminate will have a lower dielectric loss tangent (Df) through the prepreg made of the resin varnish containing the polymer composite material of the present invention. The resin varnish containing the polymer composite material of the present invention (that is, the low dielectric resin composition of the present invention) shows excellent dielectric properties and / or thermal properties.
[0159] It can be seen from Table 8 that the lower the H / S ratio of the resin varnish (that is, the low dielectric resin composition of the present invention), the lower the peel strength. Specifically, the laminated structure of Experimental Example E10 has a lower H / S ratio of the resin varnish (100 / 50) and a lower peel strength (1.61lbf / in). In addition, it can be seen from Table 8 that the laminated structure of Experimental Example E11 has a lower peel strength (2.0lbf / in) than the laminated structure of Experimental Example E8. This indicates that the resin varnish containing a second styrene copolymer having a weight average molecular weight of less than 80,000Da and a viscosity of less than 521.4Pa·s has better peel strength. Therefore, preferably, in some embodiments, the H / S ratio of the low dielectric resin composition is greater than 100 / 50, preferably greater than 100 / 35 to 100 / 10. In some embodiments, the weight average molecular weight of the second styrene copolymer is preferably less than 80,000 g / mol, preferably in the range of 40,000 to 60,000 g / mol. In some embodiments, the viscosity of the second styrene copolymer is preferably less than 521.4 Pa.s, preferably in the range of 114.8 Pa.s to 327.4 Pa.s. Therefore, in addition to excellent thermal stability and electrical performance, the metal foil laminate comprising the prepreg made from the low dielectric resin composition of the present invention can also have high peel strength and good reliability.
[0160] According to the various tests mentioned above, it can be seen that the low dielectric resin composition of the present invention or the low dielectric resin composition comprising the polymer composite material of the present invention has good electrical performance. The metal foil laminate or prepreg made from the low dielectric resin composition of the present invention or the low dielectric resin composition comprising the polymer composite material of the present invention will have good electrical performance. In some embodiments, the low dielectric resin composition of the present invention or the low dielectric resin composition comprising the polymer composite material of the present invention has good processability. The low dielectric resin composition of the present invention or the low dielectric resin composition comprising the polymer composite material of the present invention still maintains good electrical performance after the heating process and / or the hot pressing process, and is cost-effective. In some embodiments, the metal foil laminate or prepreg made from the low dielectric resin composition of the present invention or the low dielectric resin composition comprising the polymer composite material of the present invention will have good thermal properties and / or mechanical properties.
[0161] Although the present invention has been described by experimental examples and according to preferred embodiments, it should be understood that the present invention is not limited to the disclosed embodiments. On the contrary, it is intended to cover various modifications and similar configurations (as will be apparent to those with ordinary knowledge in the art). Therefore, the scope of the attached claims should be given the broadest interpretation to cover all such modifications and similar configurations.
Claims
1. A polymer composite material for preparing a low dielectric resin composition, comprising: a first styrenic copolymer having a weight average molecular weight of less than 20,000 g / mol; as well as a second styrenic copolymer having a weight average molecular weight greater than 20,000 g / mol, The weight ratio of the first styrene-based copolymer to the second styrene-based copolymer is 5 / 95 to 95 / 5, and the low dielectric resin composition has a dielectric loss tangent (Df) less than or equal to 0.00200.
2. A polymer composite material for preparing a low dielectric resin composition, comprising: a first styrenic copolymer that is liquid at 25°C; and a second styrenic copolymer, solid at 25°C, The weight ratio of the first styrene-based copolymer to the second styrene-based copolymer is 5 / 95 to 95 / 5, and the low dielectric resin composition has a dielectric loss tangent (Df) less than or equal to 0.00200.
3. The polymer composite of claim 2, wherein the first styrenic copolymer has a weight average molecular weight of less than 10,000 g / mol.
4. The polymer composite material of claim 2, wherein the first styrenic copolymer is a styrenic block copolymer.
5. The polymer composite material of claim 2, wherein the first styrene copolymer is a styrene-butadiene-styrene triblock copolymer (SBS), and a molar ratio of a 1,2-bonded structure to a 1,4-bonded structure contained in the butadiene block of the styrene-butadiene-styrene triblock copolymer (SBS) is 3:1 to 7:
1.
6. The polymer composite material of claim 2, wherein the second styrenic copolymer is a styrene-butadiene-styrene triblock copolymer (SBS) having a weight average molecular weight of less than 80,000 g / mol. 7 . The polymer composite material of claim 6 , wherein the second styrenic copolymer has a weight average molecular weight of 40,000 to 60,000.
8. The polymer composite material of claim 2, wherein the viscosity of the second styrenic copolymer is in the range of 114.8 Pa·s to 327.4 Pa·s.
9. The polymer composite material of claim 2, wherein the weight ratio of the first styrenic copolymer to the second styrenic copolymer is 25 / 75 to 80 / 20.
10. A method for using a polymer composite material, comprising: A metal foil laminate is produced using a polymer composite material to form a mixture including a hydrocarbon resin, wherein the polymer composite material comprises: a first styrenic copolymer having a weight average molecular weight of less than 20,000 g / mol; and a second styrenic copolymer having a weight average molecular weight greater than 20,000 g / mol, The weight ratio of the first styrene-based copolymer to the second styrene-based copolymer is 5 / 95 to 95 / 5, and the metal foil laminate has a dielectric loss tangent (Df) less than or equal to 0.00200.
11. A low dielectric resin composition comprising: A hydrocarbon resin; a first styrenic copolymer having a weight average molecular weight of less than 20,000 g / mol; as well as A second styrenic copolymer has a weight average molecular weight greater than 20,000 g / mol.
12. A low dielectric resin composition comprising: A hydrocarbon resin; a first styrenic copolymer that is liquid at 25°C; and A second styrenic copolymer is solid at 25°C.
13. The low dielectric resin composition according to claim 12, wherein the hydrocarbon resin comprises: 0 to 40 mol% of the repeating unit (A) is derived from a bridged ring monomer compound; 15 to 92 mol% of the repeating unit (B) is derived from a monovinyl aromatic compound; as well as 8 to 80 mol% of the repeating units (C) are derived from divinyl aromatic compounds.
14. The low dielectric resin composition according to claim 12, wherein the content of hydrogen atoms in the reactive double bonds of the hydrocarbon resin is in the range of greater than or equal to 2.3% and less than 6.6%.
15. The low dielectric resin composition of claim 12, wherein the low dielectric resin composition comprises more than 53 wt% of the hydrocarbon resin based on the total weight of the low dielectric resin composition. 16 . The low dielectric resin composition of claim 12 , wherein a weight ratio of the hydrocarbon resin to the sum of the first styrene-based copolymer and the second styrene-based copolymer is in a range of greater than 100 / 50 and less than or equal to 100 / 10. 17 . The low dielectric resin composition as claimed in claim 12 , further comprising an additive, wherein the additive is selected from the group consisting of an initiator, a flame retardant, an inorganic filler, a cross-linking aid, and any combination thereof.
18. A prepreg made from a low dielectric resin composition comprising the polymer composite material according to claim 2.
19. The prepreg according to claim 18, prepared using a method comprising the steps of: Providing a resin varnish comprising the low dielectric resin composition, wherein the low dielectric resin composition comprises the polymer composite material as claimed in claim 2; dipping a fiber substrate into the resin varnish to form a mixture; and The mixture is heated to 100-180° C. to obtain the prepreg in a semi-cured state.
20. The prepreg according to claim 19, wherein the fiber substrate is a glass fiber cloth having a dielectric loss tangent (Df) less than or equal to 0.0030.
21. A metal foil laminate comprising the prepreg according to claim 18.